2018
DOI: 10.1021/jacs.8b06021
|View full text |Cite
|
Sign up to set email alerts
|

Eu2+ Site Preferences in the Mixed Cation K2BaCa(PO4)2 and Thermally Stable Luminescence

Abstract: Site preferences of dopant Eu on the locations of K, Ba, and Ca in the mixed cation phosphate KBaCa(PO) (KBCP) are quantitatively analyzed via a combined experimental and theoretical method to develop a blue-emitting phosphor with thermally stable luminescence. Eu ions are located at K2 (M2) and K3 (M3) sites of KBCP, with the latter occupation relatively more stable than the former, corresponding to emissions at 438 and 465 nm, respectively. KBCP:Eu phosphor exhibits highly thermal stable luminescence even up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
279
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 482 publications
(296 citation statements)
references
References 39 publications
11
279
0
Order By: Relevance
“…The PLE, PL, together with DR spectra of LSA:0.02Eu 2+ are shown in Figure A. Two distinct characteristic excitation bands of Eu 2+ ions ranging from 250 to 350 nm are observed, which originate from the ground state 4 f 7 to the higher‐lying and lowest lying 4 f 6 5 d 1 states transition of Eu 2+ . It is also found that the PLE is in accordance with the DR spectrum.…”
Section: Resultsmentioning
confidence: 62%
“…The PLE, PL, together with DR spectra of LSA:0.02Eu 2+ are shown in Figure A. Two distinct characteristic excitation bands of Eu 2+ ions ranging from 250 to 350 nm are observed, which originate from the ground state 4 f 7 to the higher‐lying and lowest lying 4 f 6 5 d 1 states transition of Eu 2+ . It is also found that the PLE is in accordance with the DR spectrum.…”
Section: Resultsmentioning
confidence: 62%
“…Especially, europium is the most widely used activator, which exhibits the property of valence fluctuation of divalent (Eu 2+ ) and trivalent (Eu 3+ ). Eu 3+ ions emit red emission due to the characteristics of 5 D 0 ‐ 7 F J (J = 0, 1, 2, 3, 4) transitions, while Eu 2+ ions present tunable color ranging from blue to red due to their 5d‐4f transition . Herein, the coexistence of Eu 2+ and Eu 3+ ions suggests a dual‐mode optical output, which would provide the possibility for multi‐dimensional anti‐counterfeiting application.…”
Section: Introductionmentioning
confidence: 93%
“…Eu 3+ ions emit red emission due to the characteristics of 5 D 0 -7 F J (J = 0, 1, 2, 3, 4) transitions, while Eu 2+ ions present tunable color ranging from blue to red due to their 5d-4f transition. [18][19][20] Herein, the coexistence of Eu 2+ and Eu 3+ ions suggests a dual-mode optical output, which would provide the possibility for multi-dimensional anti-counterfeiting application. In fact, the manipulation of the appearance of Eu 2+ and Eu 3+ ions in a single host matrix has been investigated in CaYAlO 4 , 21 23 It is believed that highly compress or highly symmetry structure compounds lead to difficulty in reduction of europium, even under reducing atmosphere for the coexistence of Eu 2+ and Eu 3+ .…”
Section: Introductionmentioning
confidence: 99%
“…Such abnormal cases are rarely reported in literature. [6,[45][46][47] The thermal sensitizinge ffect is explained to be relatedw ith the ther- mal excitation of the trapped electrons at defect levels, [45,48] thereafter the energy wastransferred to activators,compensating the emissionl oss caused by normal thermalq uenching. The overall thermale mission behavior is the consequence of the competition between these two effects.…”
Section: In-situ High-temperature Photoluminescencementioning
confidence: 99%
“…The new generationo fs olid state lighting is white light emitting diodes( WLEDs), which possesses the apparent advantages of high brightness, low power consumption, long duration, low fabrication cost and environmental friendliness. [1][2][3][4][5][6] The white light can be generated through the combination of the blue emission from an InGaN chip and the yellow emission from the Y 3 Al 5 O 12 :Ce 3 + phosphor,w hich is so-called phosphorconverted (PC) WLEDs. However,i ts uffers from the high correlated colour temperature (CCT % 7750 K) and low colourr endering index (CRI < 80) due to the insufficient red component (> 600 nm), which may limit its performance in,s uch as, general illumination and medical lighting.…”
Section: Introductionmentioning
confidence: 99%